Dual-Wavelength Spectroscopy of a Metallic-Grating-Coupled Surface Plasmon Resonance Biosensor - Farshid Bahrami; J. Stewart Aitchison; Mo Mojahedi (IEEE Photonics Journal, 2015)
A novel approach is proposed to decouple the surface and bulk effects in surface plasmon resonance (SPR) biosensors. This method is based on a metallic-grating-based SPR in which a sensor is efficiently optimized to excite three surface plasmon waves at two different wavelengths. Decoupling surface and bulk effects can be realized using this technique by tracing the resonance angle variations corresponding to each excited mode. To optimize the sensor, a genetic algorithm is applied, and finally, the performance of the sensor is compared with the conventional single-interface SPR biosensor.